EFEKTIVITAS PENERAPAN PRINSIP-PRINSIP PEMBIAYAAN PENDIDIKAN DI KABUPATEN REMBANG - Wijayanti, Dwi Rahayu; Lestari, Hendang Zeta; Astuti, Cahyo Puji; Nurkolis, Nurkolis (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The principles in managing education funds consist of the principles of justice, the principles of efficiency, the principles of transparency and the principles of public accountability. The aim of this research is to determine the effectiveness of implementing the principles of financing junior high school education in Rembang Regency. This research method is quantitative and qualitative descriptive research. The research was conducted at three junior high schools in Rembang Regency using purposive sampling techniques. The subjects of this research were the school principal and school treasurer. The validity of the research uses a dual method, namely interviews and filling out questionnaires. The results of this research are: (1) the application of the principles of justice in education financing in Rembang Regency is in the